The DOTS strategy in China: results and lessons after 10 years - Xianyi Chen; Fengzeng Zhao; Hongjin Duanmu; Liya Wan; Lixia Wang; Xin Du; Chin Daniel P. (Bulletin of the World Health Organization, 2002)
OBJECTIVE: To analyse the five-point tuberculosis (TB) strategy, DOTS, 10 years after its implementation in one-half of China's population, and to suggest lessons for future implementation of the DOTS strategy. METHODS: We analysed trends in case-finding and treatment outcome over time following implementation of the DOTS strategy in each county, using routine reporting data from the Infectious and Endemic Disease Control (IEDC) project (1991 - 2000). We also determined the proportion of counties with different levels of case-finding for the fifth and sixth years of DOTS implementation. FINDINGS: From 1991 to 1995, DOTS expanded rapidly to cover more than 90% of target population and counties. By 2000, 8 million TB suspects had received free diagnostic evaluation: 1.8 million TB cases were diagnosed, free treatment was provided to 1.3 million smear-positive cases, and more than 90% were cured. During DOTS implementation, the percentage of previously treated cases decreased among all smear-positive cases and treatment outcomes improved. Despite these achievements, the detection rate for new smear-positive cases in the project was estimated to be only 54% in 1998, and 41.2% of the counties had a below average or low level of case-finding (with substantial variation between provinces). CONCLUSIONS: The IEDC project demonstrated that it is feasible to rapidly expand DOTS on a large scale. The global target of an 85% cure rate was quickly achieved, and the level of drug-resistance was probably reduced by this project. However, case-detection did not reach the 70% global target, and more research is needed on how to enhance this.